Possible actions of public and private actors towards regenerative development of businesses, in future scenarios (2022)
This study objective is to contribute to the analysis of multi-stakeholder actions to promote green and regenerative businesses while contributing to the lagging Sustainable Development Goals (SDG) targets. The methodology of future scenarios was used to develop narratives and a retrospective timeline from 2030 to the present. Risks, opportunities and patterns of action towards sustainable futures in Bolivia are identified as main findings, clarifying in each case, which of the SDG targets is being contributed to. Then, immediate, medium and long-term actions needed, and recommendations are determined from the multi-stakeholder perspective which implies working in a coordinated manner throughout the following years, towards business models that contribute to sustainable development and prioritize regenerative perspectives while promoting the most lagging SDG targets as an externality of these actions.